2021
DOI: 10.1002/cam4.3986
|View full text |Cite
|
Sign up to set email alerts
|

A five‐gene signature is a prognostic biomarker in pan‐cancer and related with immunologically associated extracellular matrix

Abstract: The tumor microenvironment (TME) is related to extracellular matrix (ECM) dynamics and has a broad fundamental and mechanistic role in tumorigenesis and cancer progression. We hypothesized that ECM regulators might play an essential role in pan‐cancer attribution by causing a generic effect through its regulation of the dynamics of ECM alteration. By analyzing data from TCGA using GSEA and univariate Cox regression analysis, we found that ECM regulator genes were significantly enriched and contributed to morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 82 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…2 H). For instance, extracellular matrix (ECM) is the dynamic foundation of tumorigenesis and cancer progression [ 25 ]. The active assemblage of ECM undoubtedly contributes to cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…2 H). For instance, extracellular matrix (ECM) is the dynamic foundation of tumorigenesis and cancer progression [ 25 ]. The active assemblage of ECM undoubtedly contributes to cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…Using gene list enrichment analysis tools (i.e., Enrichr [ 30 ]), we found some shared molecular pathways belonging to specific cancer signatures, such as hypoxia, glycolysis, and epithelial–mesenchymal transition pathways, with the latter being the most representative one, with seven genes ( Figure 4 b). Interestingly, among the seven genes upregulated by ADAR2 in both of the GBM cell lines appeared ADAM12, MMP1, and SERPINE1, which were recently identified as key extracellular matrix (ECM) regulator genes in several cancer types [ 31 ]. Moreover, ADAM12 was previously identified among the ADAR2-edi-miR-589-3p-modulated genes [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although less is known about the direct role of ADAM12 in CPI response, it is highly expressed by cancer associated fibroblasts CAFs-as shown through single cell sequencing studies and bulk tumor profilingas a driver of feed forward TGF-β signaling, has been shown to act as a T cell co-stimulatory molecule expressed on some regulatory T cells, and has been identified in a signature of negative response to ICI in melanoma [52][53][54][55][56][57] . Of note, in colorectal cancer, where single cell sequencing demonstrated high ADAM12 expression in CAFs 58 , as well as urothelial carcinoma, TGF-β signaling from CAFs has been shown to drive T cell exclusion, a hallmark of low response to ICI [59][60][61][62][63] .…”
Section: Discussionmentioning
confidence: 99%